A Possible Trifunctional β-Carotene Synthase Gene Identified in the Draft Genome of Aurantiochytrium sp. Strain KH105 - Iwasaka, Hiroaki; Koyanagi, Ryo; Satoh, Ryota; Nagano, Akiko; Watanabe, Kenshi; Hisata, Kanako; Satoh, Noriyuki; Aki, Tsunehiro (Genes, 2018)
Labyrinthulomycetes have been regarded as a promising industrial source of xanthophylls, including astaxanthin and canthaxanthin, polyunsaturated fatty acids such as docosahexaenoic acid and docosapentaenoic acid, ω-3 oils, and terpenic hydrocarbons, such as sterols and squalene. A Thraustochytrid, Aurantiochytrium sp. KH105 produces carotenoids, including astaxanthin, with strong antioxidant activity. To gain genomic insights into this capacity, we decoded its 97-Mbp genome and characterized genes for enzymes involved in carotenoid biosynthesis. Interestingly, all carotenogenic genes, as well as other eukaryotic genes, appeared duplicated, suggesting that this strain is diploid. In addition, among the five genes involved in the pathway from geranylgeranyl pyrophosphate to astaxanthin, geranylgeranyl phytoene synthase (crtB), phytoene desaturase (crtI) and lycopene cyclase (crtY) were fused into single gene (crtIBY) with no internal stop codons. Functionality of the trifunctional enzyme, CrtIBY, to catalyze the reaction from geranylgeranyl diphosphate to β-carotene was confirmed using a yeast assay system and mass spectrometry. Furthermore, analyses of differential gene expression showed characteristic up-regulation of carotenoid biosynthetic genes during stationary and starvation phases under these culture conditions. This suggests genetic engineering events to promote more efficient production of carotenoids. We also showed an occurrence of crtIBY in other Thraustochytrid species.